Knowledge, Awareness and Practice of Opioid Analgesics in Dental Management Among Undergraduates- A Questionnaire Based Study - AHMED M, ASHFAQ; GANAPATHY, DHANRAJ; PANDURANGAN, KIRAN KUMAR (The journal of contemporary issues in business and government, 2020)
Opioid analgesics are prescribed by dentists either as an adjunct or as a definitive treatment for pain management and also for some common dental diseases in which they can relieve pain when used appropriately. Nonsteroidal antiinflammatory drugs (NSAIDs) are the preferred analgesic agent by the majority of dentists when compared with opioid analgesics, because they inhibit inflammatory reactions in addition to providing analgesia. The appropriate and inappropriate use of opioid analgesics can lead to serious adverse drug events and these drugs have the potential to be misused and abused including overdose. The study was conducted among the dental undergraduates. Data collection was done by the use of online questionnaire forms that had 13 questions regarding the use of opioid analgesics in dental management. Google form was used for data collection from the surveyors.Statistical test was run using chi- square test with statistical analysis software SPSS version 23 by IBM. From the results of the study we can observe that 57% of the participants do not prescribe opioid analgesics to their patients. 62% of the participants have known that opioids can be used as a medication to relieve pain after a dental treatment. 65% of the participants consider tramadol hydrochloride to be the safest drug, 19% consider hydrocodone as the safest drug and 16% consider codeine as the safest drug among all the opioids and the results were statistically not significant. Higher interest was observed among the interns(34%) to prescribe opioids to their patients post dental treatment and the results were statistically significant. Thus it can be concluded that opioids when used in appropriate doses in the supervision of the dentist can reduce the side effects and produce excellent analgesic effect in dental management.